IMPORTANCE OF ENGLISH LANGUAGE IN MODERN EDUCATION - Ziyoda Nazarova Faxriddinovna (Journal of new century innovations, 2024)
In this article, the author explores the pivotal role of the English language in modern pedagogy, focusing on its status as a global language, its impact on educational systems, and the benefits of bilingual education. Drawing upon empirical research, theoretical frameworks, and practical insights, the article provides a comprehensive analysis of the multifaceted dimensions of English language instruction in the contemporary educational landscape.